Back Pain in Adolescent Athletes: Results of a Biomechanical Screening - Mueller, Steffen; Mueller, Juliane; Stoll, Josefine; Cassel, Michael; Hirschmüller, Anja; Mayer, Frank (Sports Medicine International Open, 2017)
The aim was to use a short biomechanical test battery to screen adolescent athletes with and without back pain to reveal relevant and possibly preventable deficits. 1 559 adolescent athletes (m/f 945/614; 13.2±1.6y) were included. Back pain was assessed (1–5: 1=no pain; 5=maximum pain) for dichotomous categorization into back pain (BP: pain>2, n=113), healthy (NBPAll: pain=1, n=1 213) and matched healthy (NBPmatched: pain=1, n=113) athletes. Athletes performed stability, performance (jumps) and trunk strength testing. The center of pressure displacement [mm], jump height [cm], peak force [N], contact time [ms] and peak torque of the trunk [Nm] were analyzed. Analysis showed a statistically significant influence of trunk strength on back pain (BP/NBPALL). Nevertheless, after including co-variables (anthropometrics, gender and training volume), there were no significant variables detectable any longer. ANOVA identified no group differences (BP/NBPmatched) in the outcome measurement for the biomechanical tests (p>0.05). This short biomechanical screening shows no sufficient differentiation in adolescent athletes for back pain. Therefore, age, training load and gender has greater relevance than strength deficits or postural control. This is challenging for further understanding of the complex conditions in young athletes with back pain.
Keywords: trunk strength; postural control; performance; training; core stability